IL-7 Promotes T Cell Viability, Trafficking, and Functionality and Improves Survival in Sepsis - Unsinger, Jacqueline (2010)
Sepsis is a highly lethal disorder characterized by widespread apoptosis-induced depletion of immune cells and the development of a profound immunosuppressive state. IL-7 is a potent antiapoptotic cytokine that enhances immune effector cell function and is essential for lymphocyte survival. In this study, recombinant human IL-7 (rhIL-7) efficacy and potential mechanisms of action were tested in a murine peritonitis model. Studies at two independent laboratories showed that rhIL-7 markedly improved host survival, blocked apoptosis of CD4 and CD8 T cells, restored IFN-γ production, and improved immune effector cell recruitment to the infected site. Importantly, rhIL-7 also prevented a hallmark of sepsis (i.e., the loss of delayed-type hypersensitivity), which is an IFN-γ– and T cell-dependent response. Mechanistically, rhIL-7 significantly increased the expression of the leukocyte adhesion markers LFA-1 and VLA-4, consistent with its ability to improve leukocyte function and trafficking to the infectious focus. rhIL-7 also increased the expression of CD8. The potent antiapoptotic effect of rhIL-7 was due to increased Bcl-2, as well as to a dramatic decrease in sepsis-induced PUMA, a heretofore unreported effect of IL-7. If additional animal studies support its efficacy in sepsis and if current clinical trials continue to confirm its safety in diverse settings, rhIL-7 should be strongly considered for clinical trials in sepsis.